See the cat : three stories about a dog - LaRochelle, David (Candlewick Press, 2020)
What happens when the book gets it wrong? Max is not a cat - Max is a dog! But much to his dismay, this book keeps instructing readers to "see the cat." How can Max get through to the book that he is a dog? In a trio of stories for beginning readers, the author introduces the excitable Max, who lets the book know in irresistibly emphatic dialogue that the text is not to his liking. The illustrator depicts the pup's reactions to the narrator and to the wacky cast of characters who upend Max's - and readers' - expectations as the three stories build to a satisfying conclusion.